2009
DOI: 10.1007/s12031-009-9248-x
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Development of the Neuromuscular Junction in Mice Lacking the γ-Subunit of Muscle Nicotinic Acetylcholine Receptor

Abstract: The mammalian muscle nicotinic acetylcholine receptor (AChR) is composed of five membranespanning subunits and its composition differs between embryonic and adult muscles. In embryonic muscles, it is composed of two α-, one β-, one δ-, and one γ-subunit; the γ-subunit is later replaced by the ε-subunit during postnatal development. This unique temporal expression pattern of the γ-subunit suggests it may play specific roles in embryonic muscles. To address this issue, we examined the formation and function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…The absence of AChR clusters was associated with excessive nerve branching, increased motoneuron survival, and aberrant distribution of the NMJ components AChE and rapsyn [Liu et al, ]. At E18.5, after the γ‐ to ϵ‐subunit switch occurred, the size of the endplate was larger in the mutant than wild type, but the fluorescence intensity of AChR staining was diminished, suggesting a decrease in the density of AChRs [Liu et al, ]. These results demonstrate that the γ‐subunit is required for the assembly of AChR clusters, which in turn play a role in the assembly of the postsynaptic apparatus at the NMJ.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of AChR clusters was associated with excessive nerve branching, increased motoneuron survival, and aberrant distribution of the NMJ components AChE and rapsyn [Liu et al, ]. At E18.5, after the γ‐ to ϵ‐subunit switch occurred, the size of the endplate was larger in the mutant than wild type, but the fluorescence intensity of AChR staining was diminished, suggesting a decrease in the density of AChRs [Liu et al, ]. These results demonstrate that the γ‐subunit is required for the assembly of AChR clusters, which in turn play a role in the assembly of the postsynaptic apparatus at the NMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al previously reported a case where non‐colocalization of NMJ proteins was also detected (Robinson et al, ). These postnatal abnormalities at the NMJ probably reflect the developmental effects of impaired prenatal neuromuscular transmission as well as an aberrant neuromuscular synaptogenesis (Liu et al, ; Liu, Sugiura, Padgett, & Lin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Without γ-subunit, neuromuscular synapses do not develop properly (3) and are abnormal in innervation patterns (4) and muscle fiber-type composition (5). In mice, the γ-subunit KO is lethal (6), and in humans, mutations in the cholinergic receptor, nicotinic, gamma (CHRNG) gene that encodes for γ-subunit are associated with lethal forms of multiple pterygium and Escobar syndromes (7)(8)(9).…”
mentioning
confidence: 99%